Development and Validation of a Multidomain Surgical Complication Classification System for Adult Spinal Deformity. Issue 4 (15th February 2021) - Klineberg, Eric O.; Wick, Joseph B.; Lafage, Renaud; Lafage, Virginie; Pellise, Ferran; Haddad, Sleiman; Yilgor, Caglar; Núñez-Pereira, Susana; Gupta, Munish; Smith, Justin S.; Shaffrey, Christopher; Schwab, Frank; et al.
Abstract : Study Design: Prospective analysis of example cases Objective: The aim of this study was to analyze the accuracy and repeatability of a new comprehensive classification system for capturing complications data in adult spinal deformity. Summary of Background Data: Complications are common in adult spinal deformity surgery. However, no consensus exists on the definition or classification of complications in adult spinal deformity surgery. The lack of consensus significantly limits understanding of complications' effects on outcomes in surgery for adult spinal deformity. Methods: Using a Delphi method, members of the International Spine Study Group, AO Spine, and the European Spine Study Group collaborated to develop an adult spinal deformity classification system. The multidomain classification system accounts for medical complications (cancer, cardiopulmonary, central nervous system, gastrointestinal, infectious, musculoskeletal, renal) and surgical complications (implant complications, radiographic complications, neurologic events, intraoperative events, and wound complications). Seventeen individuals ("event readers"), including spine surgeons, trainees, and research coordinators, used the new classification system two separate times to analyze complications in ten example cases. The accuracy and repeatability of the classification system were subsequently calculated based on the providers' responses for the example cases. Results: The 10 example cases included 22 complications. Nearly 95% of complications were captured by >95% of the event readers. The system demonstrated good repeatability of 86.9% between the first and second set of responses provided by event readers. Conclusion: The ISSG-AO Multi-Domain Spinal Deformity Complication Classification System for Adult Spinal Deformity demonstrated good accuracy and repeatability among both surgeons and research coordinators in capturing complications in adult spinal deformity surgery. The ISSG-AO system may be applied to help better understand the impact of complications on outcomes and costs in adult spinal deformity surgery. Level of Evidence: 5 Abstract : Supplemental Digital Content is available in the textThe International Spine Study Group, AO Spine Deformity Knowledge Forum, and European Spine Study Group developed a complications classification system for adult spinal deformity surgery. A validation study of the system was performed. Results show the system is accurate and reliable in tracking adult spinal deformity surgical complications.